An Analysis of Students’ Grammatical Errors in Writing Narrative Texts - Prihandani, Ayu Mirah (Universitas Pendidikan Ganesha, 2023)
Senior high school students still make a large number of errors related to grammar when they have writing narrative text. This study aimed to analyze the types of grammatical errors, identifying the sources of errors, and knowing the writing difficulties commonly faced by the tenth grade students of senior high school in their narrative texts. Descriptive qualitative method was used in this study. There were two kinds of data being used namely quantitative data and qualitative data. There were three different instruments applied such as, the teacher, writing test, and questionnaires. There were only 23 narrative texts collected and analyzed. Based on the error analysis, there were 308 grammatical errors classified into four types, namely ‘omission’, ‘misformation’, ‘addition’, and ‘misordering errors’ in students’ narrative texts. ‘Misformation errors’ are the biggest number of errors there were 131, the most dominant errors are ‘misformation of alternating form errors’. The errors occured because of the students’ interlingual and intralingual transfer. There were cognitive problem that made the students feel difficult in writing narrative texts because of their lack of knowledge of English grammar and vocabularies.